Transcriptional and Metabolic Responses of Maize Shoots to Long-Term Potassium Deficiency - Xiong, Wangdan; Wang, Yujian; Guo, Yongzhen; Tang, Wei; Zhao, Yiran; Yang, Guofeng; Pei, Yuhe; Chen, Jingtang; Song, Xiyun; Sun, Juan (Frontiers in Plant Science, 2022)
Potassium is important for plant growth and crop yield. However, the effects of potassium (K+) deficiency on silage maize biomass yield and how maize shoot feedback mechanisms of K+ deficiency regulating whole plant growth remains largely unknown. Here, the study aims to explore the maize growth and transcriptional and metabolic responses of shoots to long-term potassium deficiency. Under K+ insufficiency condition, the biomass yield of silage maize decreased. The transcriptome data showed that there were 922 and 1107 differential expression genes in DH605 and Z58, respectively. In the two varieties, 390 differently expressed overlapping genes were similarly regulated. These genes were considered as the fundamental responses to K+ deficiency in maize shoots, with many stress-induced genes involved in transport, primary and secondary metabolism, regulation, and other processes involved in K+ acquisition and homeostasis. Metabolic profiles indicated that most amino acids, phenolic acids, organic acids, and alkaloids were accumulated in shoots under K+ deficiency condition and part of the sugars and sugar alcohols also increased. It revealed that putrescine and putrescine derivatives were specifically accumulated under K+ deficiency condition, which may play a role in feedback regulation of shoot growth. These results confirmed the importance of K+ on silage maize production and provided a deeper insight into the responses to K+ deficiency in maize shoots.